DOCK4 is a Novel Prognostic Biomarker and Correlated with Immune Infiltrates in Colon Adenocarcinoma - Xie, Xingjiang; Lu, Yi; Wang, Bo; Yin, Xiaobin; Chen, Jianfeng (Combinatorial Chemistry & High Throughput Screening, 2024)
Background: Dedicator for cytokinesis 4 (DOCK4) is a guanine nucleotide exchange factor (GEF) for the small GTPase Rac1. However, the functions of DOCK4 concerning the tumor microenvironment (TME) in colon adenocarcinoma (COAD) remain uncertain. Methods: The TIMER and GEPIA databases were used to analyze the DOCK4 expression between COAD tissues and adjunct normal tissues. The PrognoScan database was used to assess the prognosis of DOCK4 expression in COAD. The co-expression networks of DOCK4 in COAD were constructed by the LinkedOmics website. Furthermore, the correlation between DOCK4 expression and TME of COAD was explored using TIMER and TISIDB databases. Finally, the clone formation assay was used to further verify the function of DOCK4 in COAD. The Western blotting assay was used to confirm the mechanism related to DOCK4 in COAD. Results: The DOCK4 expression was different significantly in COAD tissues and paracancerous tissues. The DOCK4 was found to play a poor role in the prognosis of patients with COAD. The DOCK4 was found to participate in the TME by promoting immune evasion of COAD. The reduction of DOCK4 expression inhibited the clone formation and Ras-associated protein 1A (Rap1A) expression of HCT116 cells. Conclusions: DOCK4 potentially plays an important role in the regulation of TME in COAD. DOCK4 facilitates the development through the Rap1A pathway, thus becoming a novel prognostic biomarker in COAD.
Keywords: prognostic biomarker